Optimalisasi Pengembangan Manajemen Usaha Dan Strategi Pemasaran Usaha Mikro Kecil Menengah (UMKM) Di Desa Kaliuling - Illahi, Salsabillah Anugerah; Mahardiyanto, Agus; Pramudita, Aulia Putri; Kurniawan, Feri; Ambarsari, Mia Retno; Anggraini, Nikensari; Wiesesha, Ardhitya; Mukaroma, Lailatul; Pangestu, Muhamad Rafi Putra; Islami, Nur Saifudin (Rumah Jurnal UNEJ, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in encouraging community economic growth supported by the times so that MSME products can be accessed widely. The factor that plays a role in the development of MSMEs is the use of digital media as a means of promoting products. The use of digital media in business activities is still very minimal by MSMEs in Kaliuling Village and several MSMEs in Kaliuling Village have not been optimal in carrying out product branding. The problems of several MSMEs in Kaliuling Village made researchers want to help MSMEs to be able to develop optimally. The method used in this research is through outreach, training and direct assistance to MSME owners. Socialization and mentoring were carried out for 16 days for MSMEs in Kaliuling Village. The results of the study show that MSME actors in Kaliuling Village are able to understand and utilize digital media to market their products and MSME owners are also assisted in designing logos as a form of enhancing visual product branding.